A Career and Development Framework for Infection Prevention and Control nurses. Issue 6 (November 2013) - Freeman, Sarah; Gray, Denise
To support Infection Prevention Services in Scotland, NHS Education for Scotland developed a Career and Development Framework for Infection Prevention and Control Nurses (IPCN). This was structured using the Post Registration Career Development Framework developed by NHS Education for Scotland (http://www.careerframework.nes.scot.nhs.uk/ ) which is based on the Career Framework for Health developed by Skills for Health 2006). This development was facilitated by NHS Education for Scotland in partnership with practitioners and educationalists, and it is supported by the Scottish government. This paper will discuss the benefits of the Career and Development Framework for IPCN, for those working or who aspire to work in infection prevention and control, managers and educationalist in NHS and non-NHS settings. The strategy for implementation in NHS boards will also be discussed.